Utilization of Qiroati Learning Method to Improve the Ability to Read the Quran at TPQ Al Mubarok Surabaya - Firmansyah, Wahyu; Hidayat, Moch Charis; Asrori, Asrori (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The holy book of the Qur'an is the word of God, which means the word of God. The Qur'an is a miracle from God and was revealed to the Prophet Muhammad through the angel Gabriel to become a guide or as a guide throughout our lives. Method is something that is very much needed in the running of a learning process, without the existence of a teaching method, it will cause a learning not to run. The purpose of this article is to focus on how to apply the Qiroati Method to the running of a learning process at TPQ Al-Mubarok and what supports or hinders the application. The method used by the researcher is in the form of research. The target is TPQ leaders, teachers and students.Data collection techniques can be obtained by observation, interviews and documentation. The results obtained in the study can be concluded as follows: 1) That the Qiro'ati Method has been proven to be very effective in its application. 2) Teachers who want to teach must have a shahadah certificate first because it is one of the supporting factors in a learning process.3. One of the obstacles at TPQ Al-Mubarok is students who do not pay attention to the material even until some are late to take part in the lessons. 4. The solution for students who are still often late is with parents dropping them off early before the lesson and using a motorized vehicle when the lesson time is approaching the lesson, and to overcome students who are naughty or do not want to pay attention to the teacher, namely with the teacher must pay special attention such as being told to be in front or if it is not successful to be given punishment such as being told to memorize short letters.